A Concise Review of Carbon Dioxide Storage in Depleted Oil Fields of Prinos in Northern Greece - Georgios C. Avraam; Konstantinos I. Vatalis (Materials Proceedings)
This paper examines the prospects of carbon dioxide capture and storage in depleted oil wells in Prinos in Kavala, Northern Greece. The need to store this gas arises from measures to minimize carbon emissions into the atmosphere to be climate-neutral by 2050 and establish an economy with net-zero greenhouse gas emissions. Greece, as part of the European Green Deal, has adopted the EU’s strategy in line with its commitment to global climate action under the Paris Agreement. The possibility of reusing the produced carbon dioxide through the oil industry is being investigated, a method that has been the subject of studies worldwide in recent decades. Incorporating evidence from studies, scientific research, and publications, the paper demonstrates that CO2 storage is an affordable and technologically compatible method with existing gas storage methods. The resulting economic and environmental benefits are highlighted, and reference is also made to the possibility of exploiting similar reservoirs in the wider area. In brief, the greenhouse effect will be reduced, and oil fields “Epsilon” and “Ammodis” are going to be extracted; hence, the financial gain should be increased. The importance of making such an investment at this particular period and the environmental and economic benefits for Greece and the EU are pointed out.